How integrated nexus planning could secure a resilient and sustainable future for Africa - Balcha, Yodit (2025)
Facing heightened climate risks and interconnected challenges, including heavy reliance on rain-fed agriculture and hydropower, many African nations require a paradigm shift in resource governance to build long-term resilience. This summary, stemming from a session at the Africa Climate Summit 2 (ACS2), reveals how the vital Water–Energy–Food–Environment (WEFE) nexus offers a powerful framework for integrated planning, replacing fragmented, siloed approaches with coordinated solutions that foster coherence across sectors. The discussion featured detailed case studies from Ethiopia, showcasing how WEFE modelling can guide strategies for sustainable food security, manage energy trade-offs in agro-industrial hubs like the Omo Gibe Basin, and inform the launch of the new WEFE Community of Practice for greater collaborative decision-making.